Prevalence and Age-Related Patterns in Health Information-Seeking Behaviors and Technology Use Among Skin Cancer Survivors: Survey Study - Michael Armando Marchetti; Liliane Sar-Graycar; Stephen W Dusza; Japbani K Nanda; Nicholas Kurtansky; Veronica M Rotemberg; Jennifer L Hay (JMIR Publications, 2022)
BackgroundInformation is an unmet need among cancer survivors. There is a paucity of population-based data examining the health information-seeking behaviors and attitudes of skin cancer survivors. ObjectiveWe aimed to identify the prevalence and patterns of health information-seeking behaviors and attitudes among skin cancer survivors across age groups. MethodsWe analyzed population-based data from the 2019 Health Information National Trends Survey 5 (Cycle 3). ResultsThe 5438 respondents included 346 (6.4%) skin cancer survivors (mean age 65.8 years); of the 346 skin cancer survivors, the majority were White (96.4% [weighted percentages]), and 171 (47.8%) were men. Most reported having ever looked for health- (86.1%) or cancer-related (76.5%) information; 28.2% stated their last search took a lot of effort, and 21.6% were frustrated. The internet was most often cited as being the first source that was recently used for health or medical information (45.6%). Compared to skin cancer survivors younger than 65 years old, those 65 years of age or older were more likely to see a doctor first for important health information (≥65 years: 68.3%;<65 years: 36.2%; P<.001) and less likely to have health and wellness apps (≥65 years: 26.4%; <65 years: 54.0%, P=.10), to have watched a health-related YouTube video (≥65 years: 13.3%; <65 years: 27.4%; P=.02), and to have used electronic means to look for information (≥65 years: 61.4%;<65 years: 82.3%, P<.001) ConclusionsSearches for health information are common among skin cancer survivors, but behaviors and attitudes are associated with age, which highlights the importance of access to doctors and personalized information sources.